PELATIHAN KEWIRAUSAHAAN KULINER MELALUI VIDEO EDUKASI DI PONDOK PESANTREN ASY-SYADZILI MALANG - Sari, Padma Adriana (Universitas Muhammadiyah Malang, 2021)
Islamic boarding schools have great potential to move the wheels of the economy by producing aspiring entrepreneurs from the thousands of students they have. Knowledge and entrepreneurial skills of Islamic boarding school students need to be continuously honed in order to produce successful entrepreneurs. Therefore, this community service activity contributes to the honing of entrepreneurial skills of students through entrepreneurship training on how to make